IMMUnity Unveiled: A Translational NETwork for tackling PARKinson's Disease – IMMUPARKNET [version 2; peer review: 2 approved] - Tamara Saksida; Alessia di Flora; Marina Romero-Ramos; Vladimirs Pilipenko; Laura Muñoz Delgado; Franca Marino; Yasemin Gursoy Ozdemir; Neda Nikolovski; Cristoforo Comi; Dale Lawson; Inês Figueira; Mitilda Gugu; et al. (Open Research Europe)
Parkinson’s disease (PD) affects more than one million people in the EU. It currently has no definitive cure, meaning that patients rely only on symptomatic treatments, which themselves are burdened by side effects. The need for advancements in both knowledge and available treatments is thus strongly felt by patients, caregivers, and health operators. This unmet need sparked the idea of orchestrating a collaborative effort via a common network – IMMUPARKNET (The role of IMMUnity in tackling PARKinson’s disease through a Translational NETwork). The IMMUPARKNET COST Action focuses on challenges in PD and its related crosstalk with immune response. Although widely recognized, the role of immunity in the onset and development of PD is still unclear. The main goal of IMMUPARKNET is to fill this knowledge gap by establishing an innovative, interdisciplinary research network and fostering exchanges of expertise among specialists from different countries and institutions. As we gather scientists and clinicians who study immunity in PD and related fields, IMMUPARKNET will establish the first nucleus of a multidisciplinary ecosystem that aims to harmonize efforts and approaches, both in research and clinical practice, to boost the development of ground-breaking treatments for PD. Through meetings, training schools, webinars, position papers, and review manuscripts, IMMUPARKNET will lead fruitful exchanges of know-how among experts in the field. The IMMUPARKNET structure revolves around 5 working groups, with a total of 157 active members from 34 different countries. Of these active members, 58.5% are young researchers, while 67.5% come from Inclusiveness Target Countries (ITC - less research-intensive COST Members; https://www.cost.eu/about/members/). IMMUPARKNET output will facilitate the improved sharing and development of research resources, straightening the road to novel treatments and identifying where existing ones can be repurposed, all, ultimately and hopefully, finding a cure for PD.